A New Study on the Effect of Pure Anatase TiO2 Film Thickness on Gentian Violet Photodegradation Under Sunlight: Considering the Effect of Hole Scavengers - Mekkaoui, Amer; Guettaf Temam, Elhachmi; Rahmane, Saad; Gasmi, Brahim (Trends in Sciences, 2022)
In this paper, pure anatase TiO2 thin films were grown on glass substrates by using sol-gel dip-coating method. To study the physical, chemical and optical properties of the deposits, TiO2 thin films were synthesized with thickness (241.5, 258.19, 230.33 and 302.35 nm). XRD patterns show that TiO2 films were grown with unique anatase phase (101). The photocatalytic test shows that film ( 302 nm) gives high photodegradation of gentian violet (GV) under sunlight irradiation due to the low number of defect sites. The increase in film thickness and the decrease of surface roughness and crystal size decrease the number of defect sites in the material which lead to low recombination rate of charge carriers. The use of Ag+ as hole scavenger increases the photocatalytic activity 4.75 times within the first hour. The photocatalysis process showed that Ag+ can be reduced on the surface of photoactivated TiO2 thin films to obtain sun-photodeposited/dip-coated AgO/TiO2 (p-n) heterojunction. HIGHLIGHTS Pure anatase TiO2 thin films were successfullysynthesized via sol-gel dip-coating method High thickness (302 nm) of TiO2 thin film exhibits high photocatalytic activity for photodegradation of GV under sunlight irradiation The presence of Ag+ in wastewater shows high photocatalytic activity of TiO2 films with 4.75 times within the first hour The possibility of sun-photodeposited/dip-coated of (p-n) AgO/TiO2 heterojunction is discussed GRAPHICAL ABSTRACT